PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM PELAKSANAAN SUPERVISI KLINIS DENGAN PENDEKATAN KOLABORATIF DI SD NEGERI 6 KOTA BANDA ACEH UNTUK MENINGKATKAN KETERAMPILAN GURU DALAM MENJELASKAN DAN MENGADAKAN VARIASI MENGAJAR - Mudasir, Mudasir; Musdiani, Musdiani; Kasmini, Lili (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research aims to find out whether the implementation of clinical supervision using a collaborative approach can improve teachers' skills in explaining and varying teacher teaching at SDN 6 Banda Aceh City. The type of research used was school action research (PTS) which was carried out at SD Negeri 6 Banda Aceh City. The subjects in this research were three teachers each teaching in classes III, IV, and V. Data was obtained by observation and documentation. Indicators are used as a measure of the success of the actions carried out in each cycle in this research. This research is said to be successful if the teacher's score for explanation skills and skills for providing variations in teaching has reached a score of 76 (Good) or greater than 90 (Very good). The research results showed that: (1) There was an increase in explaining skills with an average increase in explaining skills from cycle I of 67.21 (fair category), in cycle II of 81.11 (good category). (2) There was an increase in skills in carrying out teaching variations with an average increase in skills in carrying out teaching variations from cycle I of 67.14 (fair category), in cycle II amounting to 81.90 (good category). With an average increase per cycle, I and II for NK teachers of 13.81%, SF teachers of 14.64% and RN teachers of 14.53%. Implementing clinical supervision with a collaborative approach can improve teachers' explaining skills and providing variations in teaching at SD Negeri 6 Banda Aceh City